Trade credit and bank information monopoly: an empirical evidence from portuguese small medium size enterprises - Almeida, Sílvia Gisela Teixeira (2015)
According previous studies, a bank can set up a higher interest rate for small company by establishing a lending relationship since information asymmetry limits competition between banks. Therefore, the bank can acquire monopoly rents from small company. However, not only banks, but also suppliers of trade credit acquire information of buyers´ creditworthiness. This paper investigates how serious is monopoly information for Portuguese SMEs. We investigate if the informed non-financial companies can extend trade credit in order to decrease the monopolistic power of lenders that might lead to hold-up problems, by analyzing companies that obtain funds from just one bank and those who obtain funds from several banks. By using a panel data of 468 Portuguese SMEs for the period of 1998-2006, our results strongly suggest that high interest rates are associated to an increase in the use of trade credit. Furthermore, the findings support the existence of a link between suppliers and customers that take time to build and leads to suppliers help their customers who experience temporary liquidity shocks. Thus, the provision of trade credit alleviates the problem of monopolies information.